Frank urbanism: Gehry takes up cities - Sequeira, M. (2021)
It is commonly assumed that Frank Gehry’s architecture is objectual and does not establish a close relationship with the site. This conviction is nourished as much by its innovative and disruptive nature, as by the way it has been presented in the specialised press. However, it is certain that Gehry himself regrets: “When people photograph my works, they usually crop the context”2. Through unprecedented research, based on in-depth archival analysis but also interaction with the author himself, Jean-Louis Cohen reveals just the opposite.